POSTMODERN TOURIST EXPERIENCE AND BICYCLE TOURISM - Kübra AŞAN; Meryem AKOĞLAN KOZAK (International Journal of Eurasia Social Sciences, 2015)
Postmodern tourism experience is investigated under the scope of bicycle tourism and cycling experiences, which are the extensions of special interest tourism. This study aims at explaning the postmodern characteristics of cycling experience as well as features of bicycle tourist and bicycle tourism. For this purpose, a case study was conducted within the scope of The 5th Karya Coasts Bicycle Tour. Participant observation and semi-structured interview techniques were utilised in order to collect data. In total 14 interviews, nine during the tour and five during the days after the tour, were conducted. The data were analyzed using content analysis. As a result of the analysis, five themes were reached. First two of these themes are the features of bicycle tourist and bicycling events, which will offer insights into bicycle tourism market. Other three themes are dedifferentiation in cycling experience, pluralisation of cycling experience and authenticity of cycling experience, which reflect the postmodern features of cycling experience. debates on abortion information on abortion nyc abortion clinics